Consumo alimentar residual: desempenho produtivo e características pós-abate de novilhos confinados - Moura, Amanda Farias de (2021)
Residual feed intake is a method used to measure the efficiency of food use by animals, regardless of the level of production, which allows the identification of animals that consume less food without affecting productive performance. Thus, the objective of this study was to evaluate the ingestive behavior, the estimated methane production, the performance and post- slaughter characteristics of steers with low, medium or high residual feed intake (RFI). They used data from studies in Laboratório de Bovinocultura de Corte of Federal University of Santa Maria, from 2006 to 2015, which comprised 157 steers information castrated feedlot and slaughtered at 24 months of age, made in a meta-analytical approach. The animals belonged to the experimental herd of the property, originating from the alternating rotational cross between the Charolais and Nellore breeds and were divided into three treatments: Low - animals with RFI values less than half (-0.5) standard deviation lower than the general average (n = 54); Medium - animals whose RFI values were located between the limits of low and high RFI animals (n = 55); High - animals that presented values of residual food consumption half (+0.5) standard deviation above the general average (n = 48). High treatment steers had a higher initial weight (302.29 kg) and Medium treatment steers had a lower average (279.31 kg), while the Low treatment did not differ (287.84 kg). The dry matter intake absolute and relative and feed conversion ratio were higher in the Alto treatment (10.95 kg / day, 2.99 kg / 100 kg of body weight and 7.84 kg DM / kg of gain, respectively), followed by Medium (9.43 kg / day, 2.66 kg / 100 kg of body weight and 6.55 kg DM / kg of gain) and Low (8.44 kg / day, 2.30 kg / 100 kg of weight) and 6.23 kg DM / kg gain). The estimated daily production of enteric methane was higher in the High treatment (248.01 L / day), lower in the Low treatment (197.03 L/ day) and the Medium treatment showed an intermediate behavior (218.46 L/ day). Steers with low RFI remained approximately 115 days in feedlot against 100 and 96 days for Medium and High. Low RFI steers showed longer carcass length (125.68 cm) compared to Medium RFI steers (123.40 cm). The relative weight of the forehead was higher in the Low RFI steers (37.22 kg / 100 kg cold carcass) compared to the High steers (36.65 kg / 100 kg cold carcass). In the relative rear weight, the reverse occurred (52.76 kg / 100 kg of cold carcass in Alto treatment and 52.05 kg / 100 kg of cold carcass in Low). Animals with Low and Medium RFI showed greater relative weight of heart, total internal fat, cardiac, renal and abomasal fat. Medium RFI animals obtained a higher relative weight of intestinal fat. While animals with Medium and High RFI had higher liver weight. High RFI animals had higher relative weights of lungs, abomasum and intestines. Marbling was higher in the High RFI treatment (6.77 points), followed by the Medium one (5.73 points) and lower in the Low one (4.90 points). Steers with negative residual feed intake demonstrate better-feed efficiency, without impairing their productive performance, but have a higher content of internal fat and less marbling in the meat.